2013
DOI: 10.1159/000342526
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms near <b><i>Interleukin 28B</i></b> Gene Are Not Associated with Hepatitis B Virus Clearance, Hepatitis B e Antigen Clearance and Hepatocellular Carcinoma Occurrence

Abstract: Background: Polymorphisms near the IL28B gene have been proposed to be strongly associated with treatment response and the rate of spontaneous clearance of hepatitis C virus infection, and treatment response of hepatitis B virus (HBV) infection. In this study, we aimed to determine whether these polymorphisms could affect natural courses of HBV infection. Methods: Genetic variations were identified through direct DNA sequencing using TaqMan assay in 1,439 patients with past or present HBV infection. Subjects i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 91 publications
4
17
1
Order By: Relevance
“…Furthermore, a recent large study from Korea illustrated that there was no correlation between IL28B and the natural history of HBV or association with development of cirrhosis and HCC. A total of 1439 patients (including 404 spontaneously recovered patients, 313 CHB patients, 305 cirrhosis patients and 417 HCC patients) were selected in this study . Moreover, a few studies also demonstrate that IL28B polymorphism does not influence outcomes of HBV infection .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a recent large study from Korea illustrated that there was no correlation between IL28B and the natural history of HBV or association with development of cirrhosis and HCC. A total of 1439 patients (including 404 spontaneously recovered patients, 313 CHB patients, 305 cirrhosis patients and 417 HCC patients) were selected in this study . Moreover, a few studies also demonstrate that IL28B polymorphism does not influence outcomes of HBV infection .…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, the association between IL28B polymorphisms and spontaneous clearance of chronic HBV infection has been investigated by several groups. However, prior studies have provided unexpected results, such as an inverse influence compared with chronic hepatitis C or indeed no association at all [17][18][19][20][21][22][23][24][25][26][27]. In contrast with HCV infection, IL28B polymorphisms seem to trigger different molecular mechanisms in terms of spontaneous and treatment-related clearance of HBV infection.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to this relationship between SNPs near the IL28B and responses to interferon-a treatment, the influence of IL28B polymorphisms on selflimited hepatitis C virus (HCV) infection has also been reported [15,16]. However, previous studies have reported that IL28B polymorphisms had an inverse influence with respect to chronic hepatitis C [17] or showed no association, with spontaneous recovery from hepatitis B viral infection [18][19][20][21][22][23][24][25][26][27]. IL28B polymorphisms seem to have different influences on the response to treatment and spontaneous clearance in hepatitis B viral infection, whereas they exhibit similar influences in hepatitis C viral infection between response to treatment and spontaneous clearance.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies did not find significant relationship between IL-28B SNPs and HBV susceptibility (Da Silva Conde et al, 2014;De Niet et al, 2012;Heidari et al, 2016;Holmes et al, 2013;Kandemir et al, 2013;Kim et al, 2013;Lee et al, 2013;Li et al, 2011;Martin-Carbonero et al, 2012;Martin et al, 2010;Ochi et al, 2011;Seto et al, 2013;Tseng et al, 2011;Zhang et al, 2014a). In contrast, other studies showed some favorable genotypes that can predict virological and serological responses in HBeAg-negative and/or positive patients (Lampertico et al, 2013;Seto et al, 2013;Sonneveld et al, 2012;Wu et al, 2012).…”
Section: Il-28bmentioning
confidence: 99%